Uma ferramenta de geração de Código VHDL a partir do Modelo de Atores utilizando o Framework Ptolemy - Medeiros, Ramon Leonn Victor (2012)
In the area of Microelectronics, one of the most difficult it is to find qualified professionals. For the training of these there is a demand for resources - human and material - which most of the time have high cost. Thus, a solution is needed as accessible to institutions and researchers, as adaptable to your needs, providing scalability and dissemination to training, without focusing on quality. From the literature, based and presenting the Ptolemy framework, developed in Java and that allows the simulation of concurrent and heterogeneous systems, and in the Actor Model were directed efforts for the development of a tool for code generation open-source and multiplatform. Thus, the aim of this work is to develop a tool to generate VHDL code based on Ptolemy Actors using the Ptolemy framework. Where, in addition to design and simulate graphically there is a difference in the possibility of modeling at different levels of abstraction and generation of the VHDL code in a hierarchical manner, presenting the process of development of the tool and the results of its use, as well as contributions.